RANCANG BANGUN WEB PENGADUAN MASYARAKAT DENGAN FRAMEWORK LARAVEL PADA NAGARI KINARI - Indrayansah, Taufik Pratama; Kurniadi, Denny; Farrel, Geovanne (Jurnal Teknik Komputer dan Informatika, 2024)
The advancement of information technology as part of globalization has become an integral part of modern society, demanding that government institutions be more transparent and facilitate access to information, especially regarding governance. Public services are a crucial element in the daily lives of citizens, supporting their activities. To provide better public services, community participation is essential to assist and improve government performance in national development efforts. Public services prioritize the public interest, ease of public affairs, and enhance public satisfaction (Riani Anisa Putri, 2022). According to Arif, Moh. Masyhur (2018), service involves providing everything needed by others in the act of serving. Service is a fundamental need of every human being and cannot be separated from life. The goal of handling complaints is to provide mechanisms, procedures, and systems that enable proper management of grievances or complaints, ensuring smooth organizational activities. Factors influencing public service conditions in Indonesia include human resources, management, public policy, public accountability, and community participation (Zunidar, Nuri Wiyono, 2023). Nagari Kinari is located in the Bukit Sundi District, Solok Regency, West Sumatra Province, covering an area of 28.86 square kilometers. According to Nagari Kinari Regulation No. 3 of 2011 on the Formation and Division of Jorong Work Areas in Nagari Kinari, this region consists of four jorongs. The support of technology and active community participation is expected to improve the quality of public services in Nagari Kinari, in line with national efforts to build a more responsive and efficient governance system.